(untitled) (Rudarsko-geološko-naftni zbornik, 2016)
The aim of this study was to determine the presence and nature of organic micropollutants in river overbank and floodplain sediments from the border between Croatia and Bosnia and Herzegovina following the catastrophic 2014 flood. The study involved ten sediment samples from the Sava and Bosna river floodplain. The volatile aromatic compounds, i.e. benzene, toluene, ethylbenzene, and xylene (BTEX), together with alkanes (the linear straight-chain alkanes and the branched alkanes, C10-C28) were determined by GC-MS method. Their estimated amounts were from <0.054 to 3.886 mg/kg, and from 10 to 406 mg/kg, respectively. Hereby, they were below allowed concentration limits for total hydrocarbons in agricultural soil of lighter texture (sandy/loam soil) which is 1000 mg/kg, whilst for heavier clayey soils the limit is 2000 mg/kg. However, their presence in itself in the investigated sediment indicates oil spill problems, whilst their possible sources might be local oil refining industries located in the local cities of Brod and Modriča in Bosnia and Herzegovina.